Chemical effects on He bubble superlattice formation in high entropy alloys. Issue 4 (August 2019) - Harrison, R.W.; Greaves, G.; Le, H.; Bei, H.; Zhang, Y.; Donnelly, S.E.
Highlights: High entropy alloys (HEAs) have complex defect diffusion characteristics and "sluggish diffusion". Novel observation of helium bubble lattice formation in the equiatomic, multicomponent alloys. Helium bubble lattice formation shows long range diffusion possible in these complex alloys. Bubble lattice parameters give key conclusions on the diffusion mechanisms in HEAs. Abstract: The probable formation mechanism of He bubble superlattices relies on long range anisotropic diffusion of self-interstitial atoms (SIAs). Here we study He ion irradiation of pure Ni and two equiatomic concentrated solid-solution alloys (CSAs) of FeNi and FeCrNiCo. It is expected from the significantly reduced diffusion of SIAs in CSAs, including high entropy alloys (HEAs), that long range anisotropic SIA migration cannot be active. We report the formation of a He bubble lattice in pure Ni, and for the first time in FeNi and FeCrNiCo systems under 30 keV He ion irradiation at room temperature. The ion dose and flux required to form a bubble superlattice increase with chemical complexity. Comparing to Ni, SIA clusters change directions more frequently due to anisotropic elementally-biased diffusion from the higher degree of chemical non-homogeneity in CSAs. Nevertheless, anisotropic 1-D diffusion of interstitial defects is possible in these complex alloys over incrementally longer time scales and irradiation doses. The sluggish diffusion, characteristic in CSAs, leads to smaller superlattice parameters and smaller bubble diameters. The chemical biased SIA diffusion and its effects on He evolution revealed here have important implications on understanding and improving radiation tolerance over a wide range of extreme conditions.